Interpopulation similarity of sex and age-related body composition variations among older adults - Marini, Elisabetta; Buffa, Roberto; Gobbo, Luis Alberto [UNESP]; Salinas-Escudero, Guillermo; Stagi, Silvia; García-Peña, Carmen; Sánchez-García, Sergio; Carrillo-Vega, María Fernanda (MDPI, 2020)
The aim of the study was to analyze sex and age-related body composition variations among older adults from the Brazilian, Italian, and Mexican population. A cross-sectional analysis was conducted in 1103 community-dwelling older adults (634 women and 469 men), aged 60 to 89 years, living in Brazil (n = 176), Italy (n = 554), and Mexico (n = 373). Anthropometric measurements were taken, BMI was calculated, and impedance measurements were obtained (resistance, R, reactance, Xc). Specific bioelectrical impedance vector analysis (specific BIVA) was applied, with the specific vector defined by impedance, or vector length (Z = (Rsp2 + Xcsp)0.5 ), and phase angle (PA = arctan Xc/R 180/π). Population, sex, and age differences in anthropometric and bioelectrical variables were evaluated by means of a two way ANOVA. The mean bioelectrical vectors were graphed by confidence ellipses and statistically compared by the Hotelling’s T2 test. The three population groups showed differences in body mass and composition (p < 0.001): the Brazilian sample was characterized by greater body dimensions, longer vectors (higher relative content of fat mass), and lower phase angles (lower skeletal muscle mass). Men were taller and heavier than women (p <0.001) but had a similar BMI (p = 0.102). They also had higher phase angle (higher skeletal muscle mass) (p < 0.001) and lower vector length (lower %FM) (p < 0.001). In the three population groups, the oldest individuals showed lower anthropometric and phase angle values with respect to the youngest ones (p <0.001), whereas the vector length did not change significantly with age (p = 0.665). Despite the differences between sexes and among populations, the trend of age-related variations was similar in the Brazilian, Italian, and Mexican older adults.
Keywords: Anthropometry; Body composition; Elderly; Specific BIVA